ACR Appropriateness Criteria® Thoracic Outlet Syndrome - Zurkiya, Omar; Ganguli, Suvranu; Kalva, Sanjeeva P.; Chung, Jonathan H.; Shah, Lubdha M.; Majdalany, Bill S.; Bykowski, Julie; Carter, Brett W.; Chandra, Ankur; Collins, Jeremy D.; Gunn, Andrew J.; Kendi, A. Tuba; et al. (Journal of the American College of Radiology, 2020)
Thoracic outlet syndrome (TOS) is the clinical entity that occurs with compression of the brachial plexus, subclavian artery, and/or subclavian vein at the superior thoracic outlet. Compression of each of these structures results in characteristic symptoms divided into three variants: neurogenic TOS, venous TOS, and arterial TOS, each arising from the specific structure that is compressed. The constellation of symptoms in each patient may vary, and patients may have more than one symptom simultaneously. Understanding the various anatomic spaces, causes of narrowing, and resulting neurovascular changes is important in choosing and interpreting radiological imaging performed to help diagnose TOS and plan for intervention. This publication has separated imaging appropriateness based on neurogenic, venous, or arterial symptoms, acknowledging that some patients may present with combined symptoms that may require more than one study to fully resolve. Additionally, in the postoperative setting, new symptoms may arise altering the need for specific imaging as compared to preoperative evaluation. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.